Décrypter le soi et le monde à travers la fantasy dans Coraline de Neil Gaiman - Alkiş, Tuğçe (Romanica Silesiana, 2021)
The aim of this paper is to show how contemporary children’s fantasy fiction offers alternative methods to children and teenagers for confronting real-life issues, such as self-discovery, sense of belonging and the process of individuation, through the analysis of Neil Gaiman’s Coraline. In his contemporary children’s fantasy book, Gaiman empowers his protagonist to explore her sense of self, overcome her insecurities and fears in a fantastic mirror-like home. This paper argues that fantasy is an effective device for explaining the complexities and dilemmas of the self and examining a child’s quest for self-discovery in the process of maturation and individuation.